Beliefs about HIV cure: A qualitative study of people living with HIV in Soweto, South Africa - Fatima Laher; Naledi Mahlangu; Mbalenhle Sibiya (Southern African Journal of HIV Medicine)
Background: Rare cases of HIV cure exist. Clinical trials of HIV cure are also underway. However, little is documented about how potential cures are perceived by African people living with HIV, although they are key stakeholders. Objectives: We explored knowledge, beliefs, and experiences about HIV cure in Soweto, South Africa.